England's summer of sport 2017. Issue 9 (19th August 2021) - Leflay, Kath; Biscomb, Kay
Abstract: The summer of 2017 heralded an interesting layering of English elite women's sports events as major competitions were held in cricket, football, rugby and hockey. Uniquely this was the first occasion when these competitions were held during the same summer period and England was the only team to participate in all four events. This presents an opportunity to examine British print media coverage of elite English women, across a range of sports tournaments during a confined season. A qualitative analysis of British print media was undertaken for each of the four tournaments. Eighty nine articles from four national newspapers were analysed and results demonstrate emergent themes of International success, Performance and Role Models. These themes are discussed in the context of an accumulation of successful coverage, third wave feminism and the framing of the achievements resulted in the portrayal of the sports women as authentic athletes.